Immunizations in the elderly: do they live up to their promise? - Herndler-Brandstetter, Dietmar (Wien Med Wochenschr, 2006)
In the 21st century, public health is not only challenged by newly emerging and re-emerging infectious diseases but also by demographic developments that are taking place in many countries. Importantly, infections in the elderly are more frequent, more severe and have distinct features with respect to clinical presentation and treatment. This is due to a decline in the functions of the immune system referred to as immunosenescence. The most important age-related changes affect the T cell system. Although this derogates the protective effect of some vaccines, vaccinations are still considered the most cost-effective medical procedure for preventing morbidity and mortality caused by infectious diseases. The present article aims at outlining the impact of infectious diseases on the elderly and summarizing the progress made in the field of vaccinations of the elderly and how age-related changes within the immune system contribute to the decreased efficacy of vaccines.